1989
DOI: 10.1111/j.1748-1716.1989.tb08626.x
|View full text |Cite
|
Sign up to set email alerts
|

Enzyme activities in type I and II muscle fibres of human skeletal muscle in relation to age and torque development

Abstract: The quadriceps muscles from 20- 30- and 70-year-old clinically healthy men and women were studied regarding maximal isometric and isokinetic muscle torque in Newton metres (Nm), morphology and enzyme activity. Biopsy specimens were taken from the vastus lateralis muscle and freeze-dried, and individual fibres were dissected out and identified as type I or type II. The activities of citrate synthase (CS), 3-OHacyl-coA dehydrogenase (HAD), lactate dehydrogenase (LDH), myokinase (MK) and creatine phosphokinase (C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
28
2
2

Year Published

1990
1990
2009
2009

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(35 citation statements)
references
References 24 publications
3
28
2
2
Order By: Relevance
“…This finding supports previous data that observed age-related decreases in CK in human skeletal muscle [141]. In contrast, a number of previous studies have observed no age-related change in CK activity in weightbearing muscles such as vastus lateralis [17], gastrocnemius [32], or ankle dorsi flexors measured using phosphorous magnetic resonance spectroscopy [93]. Of interest in the Lanza and others [93] study is that both the rate of PCr hydrolysis during the first 6 s of a 60-s maximal isometric contraction of the ankle dorsi flexors and the overall and peak glycolytic rate were significantly faster in young (20-35 years) versus older (65-80 years) men.…”
Section: Efficiency Of Metabolic Pathwayssupporting
confidence: 91%
See 1 more Smart Citation
“…This finding supports previous data that observed age-related decreases in CK in human skeletal muscle [141]. In contrast, a number of previous studies have observed no age-related change in CK activity in weightbearing muscles such as vastus lateralis [17], gastrocnemius [32], or ankle dorsi flexors measured using phosphorous magnetic resonance spectroscopy [93]. Of interest in the Lanza and others [93] study is that both the rate of PCr hydrolysis during the first 6 s of a 60-s maximal isometric contraction of the ankle dorsi flexors and the overall and peak glycolytic rate were significantly faster in young (20-35 years) versus older (65-80 years) men.…”
Section: Efficiency Of Metabolic Pathwayssupporting
confidence: 91%
“…In younger individuals, it has been observed that, relative to similar-aged men, women display: [17] The limited data available suggest that both men and women can both increase their anaerobic capacities signif- icantly in response to anaerobic training [98,155].…”
Section: Gendermentioning
confidence: 99%
“…The absolute values for AK activity of our adult subjects is consistent with other reports (39,40), and to our knowledge, The effect of age on muscle OGDH and CPT activity. *Significantly different (p Ͻ 0.04) OGDH activity between children (n ϭ 19) and adults (n ϭ 12).…”
Section: Discussionsupporting
confidence: 80%
“…CK activity has also been reported to be significantly higher in fast glycolytic than in slow oxidative muscle fibers (59), although others find no difference (9). This discrepancy might be explained by our observation that CK activities in rat skeletal muscles change with age in soleus muscle (Table 2).…”
Section: Discussioncontrasting
confidence: 55%